2015
DOI: 10.1016/j.ijsu.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of preparation with rhTSH or thyroid hormone withdrawal using 131 I-whole body scans to identify metastases of differentiated thyroid cancer

Abstract: In contrast to previously published data, this study couldn't found any differences in the sensitivity of rhTSH or THW for the preparation of DTC patients undergoing (131)I imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…The present results showed that dTAT NP-NIS inhibits cell growth and induces cellular apoptosis in TPC-1 cells. At present, a comprehensive therapeutic method for PTC involves surgery assisted by endocrinotherapy and radioactive I-131 treatment (22). Located on the epithelial cell membrane, NIS is a type of glycoprotein, whose genes are on the short arm of chromosome 19 (23).…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed that dTAT NP-NIS inhibits cell growth and induces cellular apoptosis in TPC-1 cells. At present, a comprehensive therapeutic method for PTC involves surgery assisted by endocrinotherapy and radioactive I-131 treatment (22). Located on the epithelial cell membrane, NIS is a type of glycoprotein, whose genes are on the short arm of chromosome 19 (23).…”
Section: Discussionmentioning
confidence: 99%